2003
DOI: 10.1063/1.1601303
|View full text |Cite
|
Sign up to set email alerts
|

Magnetron-type radio-frequency plasma control yielding vertically well-aligned carbon nanotube growth

Abstract: In order to understand the effects of plasma parameters on the nanotube formation and further controlled growth, we have investigated the optimal growth condition using a rf plasma-enhanced chemical vapor deposition method. The magnetic field introduced for a magnetron discharge enhances the nanotube growth as a result of the plasma-density increment and the self-bias reduction of a rf electrode. It is also found that the optimum ion flux and ion bombardment energy is a key parameter for the uniform, well-alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 21 publications
0
25
2
Order By: Relevance
“…The total pressure was kept at 50 Pa by adjusting the pumping rate of the rotary pump throughout this experiment. Lower H 2 concentrations (0 and 3 sccm) led to larger diameters and wider (n,m) distributions with (6,5), (7,5), (7,6), (8,4), (8,6), and (8,7) (Figures 6a and b). On the other hand, the 7-sccm H 2 concentration yielded the narrowest (n,m) distribution with a dominant peak corresponding to the (6,5) tube (Figure 6c).…”
Section: Catalytic Reaction Controlmentioning
confidence: 97%
See 4 more Smart Citations
“…The total pressure was kept at 50 Pa by adjusting the pumping rate of the rotary pump throughout this experiment. Lower H 2 concentrations (0 and 3 sccm) led to larger diameters and wider (n,m) distributions with (6,5), (7,5), (7,6), (8,4), (8,6), and (8,7) (Figures 6a and b). On the other hand, the 7-sccm H 2 concentration yielded the narrowest (n,m) distribution with a dominant peak corresponding to the (6,5) tube (Figure 6c).…”
Section: Catalytic Reaction Controlmentioning
confidence: 97%
“…Figures 8a-c show the PLE maps of the as-grown SWNTs as a function of t g . It is found that the d t distribution just after the incubation (2 sec) is relatively narrow and the main diameter is about 0.8 nm with (6,5), (7,5), (7,6), (8,4), and (9, 2) dominant chiralities (Figure 8a). Then, the relatively large d t (0.95 nm) SWNTs ((8, 6) and (9, 4)) initiate their growth at 5 sec (Figure 8b).…”
Section: Gas Phase Reaction Controlmentioning
confidence: 99%
See 3 more Smart Citations